2020
DOI: 10.1016/j.jamda.2020.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Care Aides Working Multiple Jobs: Considerations for Staffing Policies in Long-Term Care Homes During and After the COVID-19 Pandemic

Abstract: The true meaning of residents' rights, 9. Brown University Long-Term Care Quality Advisor; 1997. p. 4. 2. McDermott CJ. Empowering the elderly nursing home resident: The resident rights campaign. Soc Work 1989;34:155e157. 3. Centers for Medicare & Medicaid Services (CMS). CMS announces new measures to protect nursing home residents from COVID 19. Available at: https://www. cms.gov/newsroom/press-releases/cms-announces-new-measures-protectnursing-home-residents-covid-19. Accessed June 3, 2020. 4. Centers for Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 2 publications
0
68
0
Order By: Relevance
“…† † † Specifically among LTCF staff members, a November 2020 survey found that only 45% of respondents were willing to receive a COVID-19 vaccine immediately once available, and an additional 24% would consider it in the future; the most frequently identified reason for vaccine hesitancy was concern about side effects (8). High staff member turnover, staff members working in multiple facilities (9), and limited resources for staff member outreach and education (10) staff members might have additional benefits for promoting vaccination among residents. Because coverage varied among jurisdictions, lessons learned from jurisdictions or individual facilities with high coverage might provide insight into strategies that could be applied more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…† † † Specifically among LTCF staff members, a November 2020 survey found that only 45% of respondents were willing to receive a COVID-19 vaccine immediately once available, and an additional 24% would consider it in the future; the most frequently identified reason for vaccine hesitancy was concern about side effects (8). High staff member turnover, staff members working in multiple facilities (9), and limited resources for staff member outreach and education (10) staff members might have additional benefits for promoting vaccination among residents. Because coverage varied among jurisdictions, lessons learned from jurisdictions or individual facilities with high coverage might provide insight into strategies that could be applied more broadly.…”
Section: Discussionmentioning
confidence: 99%
“…3 As a result, many PSWs need to work multiple parttime jobs to earn a living wage. 3,70,71 The conditions of work within LTC homes and the difficulties in both promoting and retaining worker in the sector have been severely exacerbated by the COVID-19 pandemic. 3 Many LTC home workers contracted SARS-CoV-2 infections themselves, with eight staff members dying of COVID-19 in the first wave and two staff members dying in the second wave to date.…”
Section: Promote Staff Entry and Retention In The Sector By Improvingmentioning
confidence: 99%
“…The single-site work order decreased work hours for health-care aides by an average of sixteen hours (Duan et al 2020). To offset the financial impacts of reduced jobs, British Columbia and Alberta mandated that employers therefore increase employee hours (Possamai 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The Alternative: Centralizing the Nursing and Support Staff Workforce It is estimated that 30 percent of health-care aides in Alberta work in multiple long-term care centres. However, Minister Shandro's single-site order does not exclude healthcare aides from working outside of long-term care facilities, which 15 percent of aides reportedly do at an average of 18 hours a week (Duan et al 2020). For example, a long-term care worker in Alberta could also work in acute care, homecare, or even a grocery store, which does little to suppress COVID-19 transmission but may be necessary for financial stability (AHS 2020a).…”
Section: Introductionmentioning
confidence: 99%